The diagnostic accuracy of faecal calprotectin and small bowel capsule endoscopy and their correlation in suspected isolated small bowel Crohn's disease. Issue 10 (October 2016) - Hale, Melissa F.; Drew, Kaye; McAlindon, Mark E.; Sidhu, Reena
Abstract : Introduction: Faecal calprotectin (FC) is less accurate at identifying inflammation in the small bowel than in the colon. Small bowel capsule endoscopy (SBCE) is a useful tool to detect small bowel inflammation. We investigated the diagnostic accuracy of FC and SBCE and their correlation in patients with suspected isolated small bowel Crohn's disease. Patients and methods: This was performed as a prospective single centre study including patients attending for SBCE with suspected small bowel Crohn's disease. Patient demographics, symptoms, medications and blood parameters were collected. Capsule endoscopy findings were analysed against calprotectin values, final diagnosis and blood parameters. Results: A total of 146 patients were included (99 females and 47 males) with a mean age of 38±14 years. FC of more than 50 mg/kg was not significantly associated with clinically relevant capsule endoscopy findings ( P =0.25), correlation coefficient was 0.11. Sensitivity, specificity, positive and negative predictive values for FC at a cut-off of more than 50 mg/kg were 88.9% [95% confidence interval (CI): 65.3–98.6], 25.0% (95% CI: 17.8–33.4), 14.3 (95% CI: 8.4–22.2) and 94.1% (95% CI: 80.3–99.3), respectively. A raised FC was not significantly associated with an elevated C-reactive protein or the presence of anaemia ( P =0.19 and 0.10, respectively). Conclusion: FC performs modestly as a screening test to exclude small bowel inflammation. However, we recommend interpretation within the overall clinical context to avoid overlooking the infrequent patient with small bowel inflammation and a negative FC.